2002
DOI: 10.1159/000065949
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Tyrosine Hydroxylase Immunoreactivity in Paraventricular and Supraoptic Neurons in Illnesses with Prolonged Osmotic or Nonosmotic Stimulation of Vasopressin Release

Abstract: Our previous studies indicated that in the human paraventricular (PVN) and supraoptic (SON) nuclei, tyrosine hydroxylase (TH) – the first and rate-limiting enzyme in catecholamine synthesis – is localized mainly in magnocellular neurons and that antemortem factors regulate its expression. The purpose of the present study was to investigate the distribution of TH-immunoreactive (TH-IR) perikarya of the hypothalami of a large sample of well-documented adult subjects without neurological, psychiatric or endocrino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 65 publications
2
20
0
Order By: Relevance
“…Similarly, no significant differences in TH expression were detected in the substantia nigra between schizophrenics and controls by reverse transcription-polymerase chain reaction [45]. The interindividual variability in TH expression could be attributed to somatic illnesses that may affect the activity of the VP neurons through osmotic and nonosmotic stimuli [19]. Indeed, the cases with the largest number of TH-IR neurons in our sample are NBB 92075 – a schizophrenic patient suffering from pulmonary hypertension/cor pulmonale – and NBB 94074 – a control subject who suffered from cardiac decompensation – i.e., both cases suffering from somatic illnesses that lead to nonosmotic stimulation of VP release due to a decrease in ‘effective’ blood volume [46,47,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, no significant differences in TH expression were detected in the substantia nigra between schizophrenics and controls by reverse transcription-polymerase chain reaction [45]. The interindividual variability in TH expression could be attributed to somatic illnesses that may affect the activity of the VP neurons through osmotic and nonosmotic stimuli [19]. Indeed, the cases with the largest number of TH-IR neurons in our sample are NBB 92075 – a schizophrenic patient suffering from pulmonary hypertension/cor pulmonale – and NBB 94074 – a control subject who suffered from cardiac decompensation – i.e., both cases suffering from somatic illnesses that lead to nonosmotic stimulation of VP release due to a decrease in ‘effective’ blood volume [46,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…We also studied the expression of tyrosine hydroxylase (TH) – the first and rate-limiting enzyme for dopamine synthesis, a neurotransmitter highly implicated in the pathophysiology of schizophrenia [17, 18]. In our previous study on mentally healthy subjects [19,] TH was found to be overexpressed in the VP neurons under clinical conditions of prolonged osmotic or nonosmotic stimulation. We focused our study on the dorsolateral part of the supraoptic nucleus (dl-SON), since this is the main source of plasma VP, and about 95% of its neurons synthesize VP in humans [20].…”
Section: Introductionmentioning
confidence: 99%
“…In a number of previous studies [3,4,5,6,7,] we described striking individual differences concerning the number and distribution of TH-IR neurons in PVN and SON among control subjects, i.e., cases without known neurological, psychiatric, or endocrinological illnesses. These differences were evident throughout the entire rostrocaudal length of PVN and SON and appeared to be related neither to age or sex of the subjects nor to postmortem interval or staining procedures.…”
Section: Introductionmentioning
confidence: 95%
“…We attributed these individual differences to antemortem factors that could influence the expression of the TH gene within the human neurosecretory neurons. Since a large number of TH-IR perikarya was observed specifically in subjects that had suffered from somatic illnesses, leading to prolonged osmotic or nonosmotic stimulation of VP release (i.e., dehydration, right-sided heart failure due to pulmonary hypertension, or liver cirrhosis), we suggested that the expression of TH within the human neurosecretory nuclei is related to the activation of VP neurons [7]. …”
Section: Introductionmentioning
confidence: 99%
“…TH activities in the central and peripheral nervous systems are subject to changes in stress, aging, osmotic stimuli and other physiological or endocrinological manipulations [2,9,22,25,34].…”
mentioning
confidence: 99%